To Write a Crime, or How to Tell a “Criminal Offence” from a “Regular Offence” (Volhynia in the Last 3rd of the 16th – the Early 17th Century) - Starchenko, Natalia (Vilnius University Open Series, 2024)
The article analyzes the rhetoric of Volhynian court records based on accusations of criminal offences. The focus is on how these sources were constructed by the interested parties, and on how the szlachta culture of violence affected this process. The author explores the arguments that the noblemen presented to reclassify criminal offences as “regular offences.” Concomitantly, she analyzes the performativity of trials as the public stage where the values treasured by the community were articulated, debated and relayed to the interested parties. This constructed “reality” formed the vision of the norm and possible life strategies of noblemen. Circulating in the court and the community, it affected the proceedings of trials and the actors’ actions outside courtroom, for example, by forcing the accused whose honor was insulted by the accusations to react according to the conventions accepted by the community. In the culture where any offence, be it real or imagined, demanded defending one’s honor, a trial was just a part of a conflict and its resolution.